2014
DOI: 10.1097/psy.0000000000000085
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Chronic and Momentary Work Stress to Cardiac Reactivity in Female Managers

Abstract: Female managers who experience chronic work stress displayed elevated cardiac reactivity during momentary stress at work. The joint assessment of chronic stress and momentary stress and their relationship to physiological functioning during work clarifies the potential health risks associated with work stress. Moreover, this wireless SPA system captures the immediate subjective context of individuals when physiological arousal occurs, which may lead to tailored stress management programs in the workplace.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Because repetitive or maintained increases in heart rate in response to stress can be associated with increases in blood pressure, it was concluded that women in the higher stress category may be at a greater risk of developing cardiovascular disease. 10 Analyses of the effects of workplace stress were also performed on data collected from 89 middle-aged male and female workers in the Belgian Job Stress Project. Stress was assessed using the JCQ.…”
Section: Stress and Workmentioning
confidence: 99%
“…Because repetitive or maintained increases in heart rate in response to stress can be associated with increases in blood pressure, it was concluded that women in the higher stress category may be at a greater risk of developing cardiovascular disease. 10 Analyses of the effects of workplace stress were also performed on data collected from 89 middle-aged male and female workers in the Belgian Job Stress Project. Stress was assessed using the JCQ.…”
Section: Stress and Workmentioning
confidence: 99%
“…All studies examining severity of acute stressors regarding social interactions found no relationship with HR [ 143 , 144 , 146 , 152 ]. Positive associations between global subjective stress and HR among healthy adults [ 148 , 152 , 154 , 155 ] were identified. Furthermore, chronic stress was found to moderate this relationship such that only among individuals with chronic stress such association was found [ 154 ].…”
Section: Resultsmentioning
confidence: 99%
“…Findings suggest that changes in heart rate activity occur prior to the experience of a panic attack, indicating that HR is a viable index of autonomic factors preceding panic attacks. Relevance to other mental health conditions is less clear; however, HR may be a marker of heightened negative affect (Daly, Delaney, Doran, Harmon, & MacLachlan, 2010) and stress reactivity (Lumley et al, 2014) more generally. This relationship holds even after controlling for age, sex, substance use, and physical activity (Daly et al, 2010; Lumley et al, 2014).…”
Section: Psychophysiological Measuresmentioning
confidence: 99%
“…Relevance to other mental health conditions is less clear; however, HR may be a marker of heightened negative affect (Daly, Delaney, Doran, Harmon, & MacLachlan, 2010) and stress reactivity (Lumley et al, 2014) more generally. This relationship holds even after controlling for age, sex, substance use, and physical activity (Daly et al, 2010; Lumley et al, 2014). HR may therefore have relevance to psychological processes underlying a number of conditions associated with elevated negative affect/stress reactivity.…”
Section: Psychophysiological Measuresmentioning
confidence: 99%